Application progress of CRISPR/Cas9 genome-editing technology in edible fungi - Zhang, Yan; Chen, Shutong; Yang, Long; Zhang, Qiang (Frontiers in Microbiology, 2023)
Edible fungi are not only delicious but are also rich in nutritional and medicinal value, which is highly sought after by consumers. As the edible fungi industry continues to rapidly advance worldwide, particularly in China, the cultivation of superior and innovative edible fungi strains has become increasingly pivotal. Nevertheless, conventional breeding techniques for edible fungi can be arduous and time-consuming. CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR-associated nuclease 9) is a powerful tool for molecular breeding due to its ability to mediate high-efficiency and high-precision genome modification, which has been successfully applied to many kinds of edible fungi. In this review, we briefly summarized the working mechanism of the CRISPR/Cas9 system and highlighted the application progress of CRISPR/Cas9-mediated genome-editing technology in edible fungi, including Agaricus bisporus, Ganoderma lucidum, Flammulina filiformis, Ustilago maydis, Pleurotus eryngii, Pleurotus ostreatus, Coprinopsis cinerea, Schizophyllum commune, Cordyceps militaris, and Shiraia bambusicola. Additionally, we discussed the limitations and challenges encountered using CRISPR/Cas9 technology in edible fungi and provided potential solutions. Finally, the applications of CRISPR/Cas9 system for molecular breeding of edible fungi in the future are explored.